COVID-19 pandemic and housing demand mortgage: Partial adjustment model approach - Ayuningtyas, Fitri Juniwati; Anggrismono, Anggrismono (Universitas Ahmad Dahlan, 2024)
One of the efforts to encourage the fulfillment of housing needs is the provision of housing both from the government and the private sector by considering the community's purchasing power. The background of this research is that the fulfillment of housing needs by both the government and the private sector has yet to be maximized while the demand for housing is relatively high. This research is still necessary because the demand for housing is still high. Increased housing demand will push house prices due to limited housing land. The problems faced focus on the relatively high demand for mortgages because even in the conditions of the COVID-19 pandemic, people still make houses their top priority. This study aims to analyze the effect of people's income, loan interest rates, the amount of housing finance, and dummy before and during the COVID-19 pandemic on housing demand mortgage. The data analysis technique in this study used multiple regression Partial Adjustment Model (PAM). The results showed that the variables of income as proxy for GDP and loan interest rates significantly affected housing demand mortgage. In contrast, the amount of housing finance and the COVID-19 dummy had no significant impact. The research implication that researchers can provide to the government is to provide policy recommendations regarding the Housing Finance Liquidity Facility (FLPP) program, which is intended for low-income communities.